2017
DOI: 10.3892/mmr.2017.6543
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cell cycle arrest by increasing GTP-RhoA levels via Taxol-induced microtubule polymerization in renal cell carcinoma

Abstract: Renal cell carcinoma (RCC) is the most common neoplasm of the kidney in adults, accounting for ~3% of adult malignancies. Understanding the underlying mechanism of RCC tumorigenesis is necessary to improve patient survival. The present study revealed that Taxol-induced microtubule (MT) polymerization causes cell cycle arrest and an increase in guanosine triphosphate-Ras homology gene family, member A (GTP-RhoA) protein expression. Disruption of Taxol-induced MT polymerization reversed GTP-RhoA expression and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous studies indicated that NCTD 24 and PTX 25 induced cell cycle arrest in multiple cancer cells. Moreover, this study next clarified whether NCTD combined with PTX induces cell cycle arrest.…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies indicated that NCTD 24 and PTX 25 induced cell cycle arrest in multiple cancer cells. Moreover, this study next clarified whether NCTD combined with PTX induces cell cycle arrest.…”
Section: Resultsmentioning
confidence: 98%
“…We began with evaluating the drug efficacy and mechanism of action in vitro. Taxol binds to the mitotic spindle apparatus and disrupts chromosomal segregation, which leads to mitotic catastrophe and cell death 21 , 36 , 37 . In vitro fluorescent imaging showed the internalization of Taxol646 in PS5A1 tumor cells after 1-h co-incubation (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the efficacy of optoBBTB for Taxol delivery in our GEMM, we first evaluated its efficacy and mechanism of action in vitro. Taxol is known to binding to the mitotic spindle apparatus, and disrupt chromosomal segregation which leads to mitotic catastrophe and cell death ( 28, 29 ). In vitro studies showed the internalization of Taxol Janelia Fluor 646 in PS5A1 glioma cells after 1-hour co-incubation.…”
Section: Resultsmentioning
confidence: 99%